2007
DOI: 10.1055/s-2007-982085
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and Kinetics of Different Heparins Binding to P- and L-Selectin

Abstract: Selectins are adhesion receptors that participate in inflammation and tumor cell metastasis. The anti-inflammatory and antimetastatic activities of heparins have been related partly to their ability to interact with P- and L-selectin. The recent findings that various heparins differ in antimetastatic activity were explained by differences in their P- and L-selectin binding ability. To obtain data to illustrate the binding characteristics, we detected for the first time the binding kinetics and affinity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Based on SPR binding analysis, Hashiguchi et al (2007) reported that the wild-type strain (IC-B) H-protein does not bind to CD46. We tested the binding kinetics of sH ICB carrying the N481Y mutation and recorded a K d of 1460 nM, an affinity similar to that seen between cell adhesion molecules (34). Thus, the single Tyr substitution at 481 confers on the H-protein the ability to bind CD46, where previously it had no interaction.…”
Section: Discussionmentioning
confidence: 97%
“…Based on SPR binding analysis, Hashiguchi et al (2007) reported that the wild-type strain (IC-B) H-protein does not bind to CD46. We tested the binding kinetics of sH ICB carrying the N481Y mutation and recorded a K d of 1460 nM, an affinity similar to that seen between cell adhesion molecules (34). Thus, the single Tyr substitution at 481 confers on the H-protein the ability to bind CD46, where previously it had no interaction.…”
Section: Discussionmentioning
confidence: 97%
“…To further validate the data obtained from the in vitro assays, the binding parameters of oritavancin and vancomycin to selected lipid II variants (lipid II, lipid II-Gly 5 , amidated lipid II, amidated lipid II-Gly 5 , lipid II-D-Lac, and amidated lipid II-D-Lac) were determined using a quartz crystal microbalance (QCM) technique (48)(49)(50).…”
Section: Oritavancin Blocks Individual Cell Wall Biosynthesis Reactiomentioning
confidence: 99%
“…After equilibration of the quartz crystals under flow conditions until they reached a constant frequency, 1 M peptide solution was added. The frequency curves allow the calculation of the kinetic binding constants as described previously (49,50).…”
mentioning
confidence: 99%
“…[18] Among this class of inhibitors is heparin, a naturally occurring polysaccharide isolated from animal tissue, which shows moderate anti-inflammatory potential in addition to a strong anti-coagulant effect. [19] This limits the extensive use of heparin in anti-inflammatory therapy due to the related risk of bleeding. However, heparinoids with reduced or no anti-coagulant properties but remaining selectin affinity have been developed.…”
Section: Introductionmentioning
confidence: 99%